Haemoptysis as the first presentation of COVID-19: a case report - Elise Peys; Dieter Stevens; Yannick Vande Weygaerde; Thomas Malfait; Laurens Hermie; Philippe Rogiers; Pieter Depuydt; Eva Van Braeckel (BMC Pulmonary Medicine, 2020)
Abstract Background Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an ongoing pandemic that profoundly challenges healthcare systems all over the world. Fever, cough and fatigue are the most commonly reported clinical symptoms. Case presentation A 58-year-old man presented at the emergency department with acute onset haemoptysis. On the fifth day after admission, he developed massive haemoptysis. Computed tomography (CT) angiography of the chest revealed alveolar haemorrhage, more prominent in the left lung. Flexible bronchoscopy confirmed bleeding from the left upper lobe, confirmed by a bronchial arteriography, which was successfully embolized. Nasopharyngeal swabs (NPS) tested for SARS-CoV-2 using real-time polymerase chain reaction (RT-PCR) repeatedly returned negative. Surprisingly, SARS-CoV-2 was eventually detected in bronchoalveolar lavage (BAL) fluid. Conclusions Life-threatening haemoptysis is an unusual presentation of COVID-19, reflecting alveolar bleeding as a rare but possible complication. This case emphasises the added value of bronchoscopy with BAL in the diagnostic work-up in case of high clinical suspicion and negative serial NPS in patients presenting with severe symptoms.